Accommodative study of public space for marginalized people / Wakhidah Kurniawati - Kurniawati, Wakhidah (Faculty of Architecture, Planning and Surveying, 2012)
A good public space must be accommodative for everyone included the marginal, the forgotten, the silent (Badshah, 1996), and an undesirable people. “Cities for the Citizen ‘(Douglas & Friedmann, 1998) serves a slogan. Accommodative public space for marginal people and marginal activities can be created when physical aspects of space can accommodate the space needs of the Forgotten (Badshah, 1996). Thus, the society will be educated to learn and share, to respect the rights of other users in the city, and consequently the physical quality of the visual city will be better because there are no annexation of space and overlapping activities.